STUDENTS OF FOREIGN LANGUAGES: A CRUCIAL FACTOR IN PRESERVING AND FOSTERING NATIONAL CULTURAL VALUES IN THE CONTEXT OF INTERNATIONAL INTEGRATION (Journal of Foreign Language Studies, 2021)
International integration is an inevitable trend as a result of a nation’s need for socio-economic development and international exchange. The international integration process takes place in all aspects of life, including education and culture. In this process, learners of foreign languages in general and Hanoi University students in particular can play a crucial role in preserving and fostering national cultural values. In order for the youth to fulfil the mission of a cultural ambassador, which teaching methods do teachers have to adopt? This paper provides an answer to this question on the basis of a study on the role of Hanoi University students. It then proposes some recommendations for raising the awareness of students’ responsibilities in preserving and fostering national cultural identity.
Keywords: national cultural identity; international integration